Comparative analysis of external load in small-sided games versus official matches among professional football players - Kaan Kaya; Barış Gürol; Selçuk Tarakcı (Physical Education of Students, 2024)
Background and Study Aim. Coaches frequently use small-sided games with numerical inequalities. However, it is unclear if these games accurately represent official matches. This study aims to identify the differences in external load between small-sided games and official matches among professional soccer players, incorporating the variance due to positional roles.